Acute Severe Ulcerative Colitis: A Case Report of Successful Management with Infliximab - Govind Shiddapur; Diksha Sabharwal; Sonali Agarwal; Uttara Shankarnarayan; Kalyan Kumar Reddy (Journal of Clinical and Diagnostic Research)
Acute Severe Ulcerative Colitis (ASUC) is a critical, life-threatening condition characterised by more than six bloody stools per day, along with systemic signs of inflammation, such as fever, tachycardia and anaemia. Despite advances in treatment, ASUC remains a significant cause of morbidity. Management typically involves corticosteroids as the first line of treatment; however, a substantial proportion of patients are steroid-refractory, necessitating escalation to rescue therapies like Infliximab (IFX) or Cyclosporine (CyA). The present case report presents the successful management of ASUC using IFX in a steroid-refractory patient. Hereby, the authors present a case report of a 23-year-old male patient presented with a 15-day history of increased stool frequency (10-15 times per day) associated with blood, mucus, abdominal pain and fever. Initial investigations, including Computed Tomography (CT) scans, colonoscopy and histopathology, confirmed a diagnosis of ASUC. Laboratory findings were consistent with severe inflammation. The patient was initially treated with intravenous hydrocortisone (100 mg every 6 hours) but showed no clinical improvement. Following this, IFX (5 mg/kg) was administered on day 6, leading to a significant reduction in stool frequency and a decrease in blood and mucus in the stools. The patient exhibited symptomatic improvement and was discharged with a plan for continued IFX therapy. A repeat episode occurred a few weeks later, but further IFX therapy again resulted in improvement. The present case highlights the importance of timely rescue therapy in steroid-refractory ASUC. IFX demonstrated rapid and sustained clinical improvement in a patient with severe disease, underscoring its efficacy as a vital therapeutic option. Close monitoring and early intervention with biologic therapy can significantly reduce the need for colectomy and improve patient outcomes in ASUC.